Sex differences in the effect of cannabinoid type 1 receptor deletion on locus coeruleus‐norepinephrine neurons and corticotropin releasing factor‐mediated responses. (16th September 2018) - Wyrofsky, Ryan R.; Reyes, Beverly A. S.; Yu, Daohai; Kirby, Lynn G.; Van Bockstaele, Elisabeth J.
Abstract: Cannabinoids are capable of modulating mood, arousal, cognition and behavior, in part via their effects on the noradrenergic nucleus locus coeruleus (LC). Dysregulation of LC signaling and norepinephrine (NE) efflux in the medial prefrontal cortex (mPFC) can lead to the development of psychiatric disorders, and CB1r deletion results in alterations of α2‐ and β1‐adrenoceptors in the mPFC, suggestive of increased LC activity. To determine how CB1r deletion alters LC signaling, whole‐cell patch‐clamp electrophysiology was conducted in LC‐NE neurons of male and female wild type (WT) and CB1r‐knock out (KO) mice. CB1r deletion caused a significant increase in LC‐NE excitability and input resistance in male but not female mice when compared to WT. CB1r deletion also caused adaptations in several indices of noradrenergic function. CB1r/CB2r‐KO male mice had a significant increase in cortical NE levels and tyrosine hydroxylase and CRF levels in the LC compared to WT males. CB1r/CB2r‐KO female mice showed a significant increase in LC α2‐AR levels compared to WT females. To further probe actions of the endocannabinoid system as an anti‐stress neuromediator, the effect of CB1r deletion on CRF‐induced responses in the LC was investigated. The increase in LC‐NE excitability observed in male and female WT mice following CRF (300 nM) bath application was not observed in CB1r‐KO mice. These results indicate that cellular adaptations following CB1r deletion cause a disruption in LC‐NE signaling in males but not females, suggesting underlying sex differences in compensatory mechanisms in KO mice as well as basal endocannabinoid regulation of LC‐NE activity. Abstract : Novel electrophysiological data in mice reveal that cannabinoid receptor (CB1r) deletion results in a significant increase in locus coeruleus‐norepinephrine (LC‐NE) excitability in male mice, but not in females. Basal differences in CB1r expression were also observed with male wild type (WT) having higher CB1r levels than female WT mice. Taken together, these data suggest that females may have less tonic endocannabinoid signaling in the LC‐NE system compared to males, potentially contributing to the increased vulnerability of females to stress‐induced psychiatric disorders.